Helicobacter pylori infection influences the severity of thrombocytopenia and its treatment response in chronic hepatitis B patients with compensatory cirrhosis: A multicenter, observational study. (2nd April 2016) - Zhang, Xiao-Hui; He, Yun; Feng, Ru; Xu, Lan-Ping; Jiang, Qian; Jiang, Hao; Lu, Jin; Fu, Hai-Xia; Liu, Hui; Wang, Jing-Wen; Wang, Qian-Ming; Feng, Fei-Er; et al.
Abstract: The role of Helicobacter pylori ( H. pylori ) infection on thrombocytopenia in chronic hepatitis B (CHB) related compensatory cirrhotic patients is unknown. We conducted an observational study to determine whether H. pylori plays a role in these patients. A total of 255 patients from three centers in China were enrolled in the study. All patients received nucleoside analogs (NA) therapy and were screened for H. pylori infection. Patients were divided into three groups based on their H. pylori infection status and the therapy administered: patients without H. pylori infection who received NA therapy alone ( N = 146); patients with H. pylori infection who received NA therapy alone ( n = 48); and patients with H. pylori infection who received H. pylori eradication combined with NA therapy ( N = 61). We observed that in CHB compensatory cirrhotic patients with H. pylori infection, the platelets count was significantly lower relative to uninfected patients (31 versus 60 × 10 9 /L, p < 0.01). During a 2-year follow-up, the elevation in platelet count was significantly higher in HBV/ H. pylori co-infected patients who received the NA and H. pylori eradication treatment compared to the other two groups ( p < 0.01). It suggested that H. pylori infection and eradication treatment combined with NA were independent risk factors associated with platelets response during treatment of thrombocytopenia in CHB compensatory cirrhosis ( p < 0.01). In conclusion, H. pylori infection may associate with thrombocytopenia in CHB compensatory cirrhosis. H. pylori eradication combined with NA treatment may prove to be beneficial to CHB compensatory cirrhotic patients with thrombocytopenia who are infected with H. pylori .